Tertiary Lymphoid Structures in Cancer: Drivers of Antitumor Immunity, Immunosuppression, or Bystander Sentinels in Disease? - Colbeck, Emily Jayne; Ager, Ann; Gallimore, Awen; Jones, Gareth Wyn (Frontiers in Immunology, 2017)
Secondary lymphoid organs are integral to initiation and execution of adaptive immune responses. These organs provide a setting for interactions between antigen-specific lymphocytes and antigen-presenting cells recruited from local infected or inflamed tissues. Secondary lymphoid organs develop as part of a genetically pre-programmed process during embryogenesis. However, organogenesis of secondary lymphoid tissues can also be recapitulated in adulthood during de novo lymphoid neogenesis of tertiary lymphoid structures (TLS). These ectopic lymphoid-like structures form in inflamed tissues afflicted by various pathological conditions, including cancer, autoimmunity, infection or allograft rejection. Studies are beginning to shed light on the function of such structures in different disease settings raising important questions regarding their contribution to progression or resolution of disease. Data show an association between tumor-associated TLS and a favorable prognosis in various types of human cancer, attracting the speculation that TLS support effective local anti-tumor immune responses. However, definitive evidence for a role for TLS in fostering immune responses in vivo are lacking, with current data remaining largely correlative by nature. In fact, some more recent studies have even demonstrated an immunosuppressive, tumor-promoting role for cancer associated TLS. In this review, we will discuss what is known about the development of cancer-associated TLS and the current understanding of their potential role in the anti-tumor immune response.